Archaeal ribonuclease P proteins have potential for biotechnological applications where precise hybridization of nucleic acids is needed. Issue 12 (2nd December 2015) - Miyanoshita, Mitsuru; Nakashima, Takashi; Kakuta, Yoshimitsu; Kimura, Makoto
Abstract: Fluorescence resonance energy transfer-based assay showed that archaeal ribonuclease P (RNase P) proteins significantly promoted DNA annealing and strand displacement. Moreover, we found that archaeal RNase P proteins could discriminate nucleotide exchanges in DNA chains via their activity accelerating DNA strand displacement, suggesting that they have potential for biotechnological application to genetic diagnosis.